UPON TYPE, FREQUENCY AND SOME CLINICAL ASPECTS OF PSYCHOTIC SYMPTOMS IN ALZHEIMER'S DISEASE - Mariana Arnaudova (Peytchinski Publishing, 2011)
Various psychotic disorders develop often at different stages of the disease. A comprehensive approach of type, frequency and clinical aspects of the psychotic disorders patients with Alzheimer's disease (AD) can optimize management of these conditions in patients with dementia. We examined 120 patients with probable AD. The routine clinical examination and observation were used to delineate the most common psychotic symptoms. Delusions, found in the explored patients were predominantly paranoid. The delusions are often short lived and lack complexity of that seen in schizophrenia. In number of cases they are difficult to be distinguished from confabulations. Hallucinations were mostly verbal, visual and tactile. Misidentification syndromes were identified in a considerable number of patients. They are often disputable or have been classified as delusions or hallucinations, depending on interpretation of psychotic phenomena. We discuss different forms of misidentification. The presence of psychotic symptoms predicts the occurrence and frequency of different forms of aggression and destructive behavior.